The use of biomarkers in the diagnosis and treatment of obstruction of the upper urinary tract in children - Seifriedová, Zuzana; Flögelová, Hana; Šarapatka, Jan; Šmakal, Oldřich; Študent, Vladimír (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2022)
Antenatal hydronephrosis, dilatation of the upper urinary tract (UUTD), is a common finding on prenatal ultrasound. One of the most common causes is ureteropelvic junction (UPJ) obstruction. Although such prenatally diagnosed UUTD resolves spontaneously in most newborns, further examination of these children is advocated to prevent possible irreversible kidney damage, and ultrasound is mainly used for this. If the dilatation persists or becomes symptomatic, it is necessary to proceed to other relatively demanding and invasive diagnostic examinations for these small patients, where the question of the right timing of indications for possible surgical solutions is still unclear. For this reason, various biomarkers have been investigated in a number of clinical trials as potential mini-invasive diagnostic tools for determining when upper urinary tract dilatation in such children poses a threat to the developing kidneys and they should be operated on, and vice versa, when to proceed conservatively. The aim of this article is to review the findings on and current issues with the use of biomarkers in the diagnosis and treatment of UPJ obstruction in children.
Keywords: Kidney; močové ústrojí; Female; dítě; biologické markery; novorozenec; Biomarkers; ženské pohlaví; obstrukce močovodu; lidé; Infant, Newborn; těhotenství; Ureteral Obstruction; Hydronephrosis; Urinary Tract; hydronefróza; Child; Pregnancy; ledviny; Humans